The Development of Appsheet-Assisted Three Finger Diagnostic Test Instrument for Identifying Miscellaneos Algebra Concept - Rahmawati, Fitri Nur; Hidayat, Wahyu; Aripin, Usman ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Misconceptions are common among students when solving mathematics problems and, if left unaddressed, may hinder their ability to understand the material. This study seeks to design and develop diagnostic test instruments—comprising questions and questionnaires—on algebra topics using the Appsheet application. The objectives are to assess the development process, feasibility, and effectiveness of the instruments, as well as to identify challenges faced during implementation. The research employed a Design Research approach with a development studies type, consisting of two stages: preliminary design and formative evaluation. The instruments underwent a one-to-one trial with three students, a small-group trial with six students, and a field test involving 33 eighth-grade students at SMP Negeri 1 Margaasih. Expert validation rated the instruments as “feasible.” Data were gathered through documentation, tests, and interviews. The instruments included 10 three-tier multiple-choice questions, a closed-ended questionnaire with 13 items, and interviews with both teachers and students. Analysis revealed that 3.9% of students understood the concepts, 8.2% exhibited positive misconceptions, 8.4% negative misconceptions, 22.1% general misconceptions, while 57.3% showed no conceptual understanding. These findings demonstrate that the instruments effectively identified algebraic misconceptions. Challenges encountered included limited school facilities for mobile device usage and occasional errors in the application when accessed simultaneously by many users, indicating the need for updates. Nevertheless, the Appsheet-assisted three-tier diagnostic test provides a feasible and promising tool for detecting misconceptions in junior high school algebra learning